2018
DOI: 10.1016/j.dadm.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Apraxia profiles—A single cognitive marker to discriminate all variants of frontotemporal lobar degeneration and Alzheimer's disease

Abstract: Introduction Apraxia is common in neurodegenerative dementias but underrepresented in clinical workup for differential diagnoses. Methods Praxis-profiles were assessed with the Dementia Apraxia Test in 93 patients with early stages of biologically supported Alzheimer's disease or frontotemporal lobar degeneration: semantic primary-progressive aphasia, nonfluent primary-progressive aphasia, and behavioral variant frontotemporal dementia. Associations with core cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…Only recently, apraxia has gotten into the focus of clinical research on the early detection and differential diagnosis of neurodegenerative dementia syndromes such as bvFTD and AD (122, 297300). Although results highly depend on the employed assessment methods and the tested praxis domains, an array of studies has now shown that patients with bvFTD show overall poorer performance in quantitative praxis tasks as well as clinical evaluations of praxis performance (297301). Regarding the affected dimensions of praxis dysfunction, evidence suggests that performance in the domains imitation of meaningless hand or limb postures, pantomime of common object-use, and particularly imitation of face-postures are each significantly reduced in early stages of bvFTD compared to healthy age-matched controls (299, 302).…”
Section: Promising Cognitive and Psychological Markers For Bvftd Beyomentioning
confidence: 99%
See 2 more Smart Citations
“…Only recently, apraxia has gotten into the focus of clinical research on the early detection and differential diagnosis of neurodegenerative dementia syndromes such as bvFTD and AD (122, 297300). Although results highly depend on the employed assessment methods and the tested praxis domains, an array of studies has now shown that patients with bvFTD show overall poorer performance in quantitative praxis tasks as well as clinical evaluations of praxis performance (297301). Regarding the affected dimensions of praxis dysfunction, evidence suggests that performance in the domains imitation of meaningless hand or limb postures, pantomime of common object-use, and particularly imitation of face-postures are each significantly reduced in early stages of bvFTD compared to healthy age-matched controls (299, 302).…”
Section: Promising Cognitive and Psychological Markers For Bvftd Beyomentioning
confidence: 99%
“…These results are particularly intriguing as patients with bvFTD show no or only minor comorbid language symptoms in clear contrast to the prototypical apraxic and aphasic patients after left-hemispheric stroke. When compared to patients with AD, bvFTD patients present with a praxis profile of similar or less severe limb apraxia (i.e., imitation of meaningless gestures and pantomime of object-use) but relatively more pronounced buccofacial [or “orofacial,” sometimes used synonymously (303)] praxis deficits with a particular impairment regarding the imitation of face postures (122, 297, 299, 301, 302). Across different samples and using diverse apraxia tests such a relative “buccofacial apraxia profile” robustly showed high diagnostic accuracy for the diagnosis of bvFTD and also stood out among several established standard neurocognitive tests and domains (including standard memory and executive tasks) regarding diagnostic accuracy for the discrimination between AD and bvFTD (122, 301).…”
Section: Promising Cognitive and Psychological Markers For Bvftd Beyomentioning
confidence: 99%
See 1 more Smart Citation
“…As a higher‐order disorder of sensorimotor integration, apraxia is commonly seen in neurological diseases, such as Alzheimer disease (AD) and stroke, and may contribute to dementia diagnosis in early stages . Among subtypes of apraxia, ideomotor apraxia is believed to reflect an impaired action production system.…”
mentioning
confidence: 99%
“…A s a higher-order disorder of sensorimotor integration, apraxia is commonly seen in neurological diseases, such as Alzheimer disease (AD) and stroke, and may contribute to dementia diagnosis in early stages. [1][2][3][4][5][6] Among subtypes of apraxia, ideomotor apraxia is believed to reflect an impaired action production system. Due to insufficient conversion to execution of motor programming, individuals with ideomotor apraxia exhibit deficits in the spatial organization, timing, and sequencing of gestural movements.…”
mentioning
confidence: 99%